An evaluation rule to manage productivity properties performance of male date palms - Abdel-Sattar Mahmoud; Al-Obeed Rashid S.; Aboukarima Abdulwahed M.; Górnik Krzysztof; El-Badan Ghada E. (Folia Horticulturae)
Male palm trees almost prominently display minute morphological variations; however, date palm growers rely on readily available pollen from unproven male genotypes without giving correct type selection any thought, which may result in low productivity and/or poor fruit quality. This study sought to develop an evaluation rule by calculating an evaluation index for managing the productivity characteristics performance of nine male date palms, which were examined for their pollen productivity, nutritional status and morphological traits from their leaves, pinnae and spathes. The findings showed that the evaluation rule for a male date palm should depend on pollen grains productivity and germination percentage traits with a weight of 5, spathe morphological traits with a weight of 4, pinnae morphological traits with a weight of 3, leaf morphological traits with a weight of 2 and leaf nutritional status with a weight of 1. The best productivity characteristics performance of male date palms was male No. 8 ‘M8’ due to its high evaluation index. The proposed evaluation index criterion will contribute to better information and analytical support for management of the date palm industry to maximise the effectiveness of germplasm conservation and exploitation, as well as procedural and methodological aspects of the analysis.